Global Analysis of DELLA Direct Targets in Early Gibberellin Signaling in Arabidopsis - Zentella, Rodolfo (American Society of Plant Biologists, 2007)
Bioactive gibberellins (GAs) are phytohormones that regulate growth and development throughout the life cycle of plants. DELLA proteins are conserved growth repressors that modulate all aspects of GA responses. These GA-signaling repressors are nuclear localized and likely function as transcriptional regulators. Recent studies demonstrated that GA, upon binding to its receptor, derepresses its signaling pathway by binding directly to DELLA proteins and targeting them for rapid degradation via the ubiquitin-proteasome pathway. Therefore, elucidating the signaling events immediately downstream of DELLA is key to our understanding of how GA controls plant development. Two sets of microarray studies followed by quantitative RT-PCR analysis allowed us to identify 14 early GA-responsive genes that are also early DELLA-responsive in Arabidopsis thaliana seedlings. Chromatin immunoprecipitation provided evidence for in vivo association of DELLA with promoters of eight of these putative DELLA target genes. Expression of all 14 genes was downregulated by GA and upregulated by DELLA. Our study reveals that DELLA proteins play two important roles in GA signaling: (1) they help establish GA homeostasis by direct feedback regulation on the expression of GA biosynthetic and GA receptor genes, and (2) they promote the expression of downstream negative components that are putative transcription factors/regulators or ubiquitin E2/E3 enzymes. In addition, one of the putative DELLA targets, XERICO, promotes accumulation of abscisic acid (ABA) that antagonizes GA effects. Therefore, DELLA may restrict GA-promoted processes by modulating both GA and ABA pathways.